Increased PCSK9 associated with cIMT in AS: A useful marker for subclinical atherosclerosis in patients with ankylosing spondylitis - Ahmet Karakoyun; Yasemin Akkubak; Mevlüt Hakan Göktepe; Pınar Diydem Yılmaz; Cengiz Kadıyoran; Mustafa Oğul; Adem Kucuk (Archives of Rheumatology, 2024)
Objectives: This study aims to investigate the relationship between proprotein convertase subtilisin/ kexin type 9 (PCSK9) levels and subclinical atherosclerosis (SA) in patients with ankylosing spondylitis (AS). Patients and methods: Between January 2022 and March 2022, a total of 56 patients (33 males, 23 females; mean age: 37.8±9.3 years; range, 20 to 60 years) who were under regular follow-up in our clinic and fulfilled the criteria of the Modified New York Diagnostic Criteria for AS and American College of Rheumatology (ACR) for AS were included. Age- and sex-matched 56 healthy volunteers (25 males, 31 females; mean age: 38.4±8.2 years; range, 20 to 60 years) were also recruited as the control group. Demographic, clinical, and laboratory data were recorded. The PCSK9 level and carotid intima-media thickness (cIMT) were evaluated using appropriate methods. Results: The mean serum PCSK9 levels in AS patients (609.3±149.9 vs. 136.3±120.8 ng/mL, p<0.001) and the mean cIMT values (0.51±0.19 vs. 0.43±0.08 mm, p=0.003) were higher than healthy controls. In the multivariate stepwise regression analysis, there was an independent relationship between SA and PCSK9 (β=0.324, p=0.001). Additionally, there was an independent relationship between carotid plaque and PCSK9 (β=0.265, p=0.006). Based on the receiver operating characteristic curve analysis, the optimal PCSK9 cut-off value for plaque was 472.0 ng/mL, sensitivity 90.9%, specificity 65.0% (area under the curve [AUC]=0.759; 95% CI: 0.660-0.857, p=0.005). The optimal PCSK9 cut-off value for SA was 459.5 ng/mL, sensitivity 63.2%, specificity 63.0% (AUC=0.625; 95% CI: 0.512-0.739, p=0.031). Conclusion: Our study showed that serum PCSK9 levels in patients with AS were higher than that in healthy individuals and were associated with SA and arterial plaque formation. In the light of these findings, PCSK9 may accelerate SA and carotid plaque formation in patients with AS, regardless of the LDL cholesterol level. There may be no relationship between PCSK9 levels and disease activity in patients with AS.